Glycometabolic reprogramming associated with the initiation of human dental pulp stem cell differentiation. (27th December 2015) - Wang, Linyan; Cheng, Li; Wang, Huning; Pan, Hongying; Yang, Hui; Shao, Meiying; Hu, Tao
Abstract: Glycometabolism, particularly mitochondrial oxidative phosphorylation (OXPHOS) and glycolysis, plays a central role in cell life activities. Glycometabolism can be reprogrammed to maintain the stemness or to induce the differentiation of stem cells, thereby regulating tissue repair and regeneration. However, research on the glycometabolism of human dental pulp stem cells (hDPSCs) remains scarce. Here, we investigated the relationship between glycometabolic reprogramming and initiation of hDPSC differentiation. We found the differentiation of hDPSCs commenced on day 3 when cells were cultured in mineralized medium. When cell differentiation commenced, mitochondria became elongated with well‐developed cristae, and the oxygen consumption rate of mitochondria was enhanced, manifested as an increase in basal respiration, mitochondrial ATP production, and maximal respiration. Interestingly, glycolytic enzyme activities, glycolysis capacity, and glycolysis reserve were also upregulated at this time to match the powerful bioenergetic demands. More importantly, hDPSCs derived from different donors or cultured in various oxygen environments showed similar glycometabolic changes when they began to differentiate. Thus, glycometabolic reprogramming accompanies initiation of hDPSC differentiation and could potentially play a role in the regulation of dental pulp repair.